2020
DOI: 10.1515/cclm-2020-0220
|View full text |Cite
|
Sign up to set email alerts
|

The value of urine biochemical parameters in the prediction of the severity of coronavirus disease 2019

Abstract: AbstractBackgroundAmong patients with coronavirus disease 2019 (COVID-19), the cases of a significant proportion of patients are severe. A viral nucleic acid test is used for the diagnosis of COVID-19, and some hematological indicators have been used in the auxiliary diagnosis and identification of the severity of COVID-19. Regarding body fluid samples, except for being used for nucleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 15 publications
9
92
4
3
Order By: Relevance
“…Clinical, laboratory, imaging, and prognostic studies as well as disease outcome analysis builds up the core knowledge necessary for any new disease. Several questions in the context of COVID-19 have been addressed including spectrum of disease severity (asymptomatic to fatal) 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical, laboratory, imaging, and prognostic studies as well as disease outcome analysis builds up the core knowledge necessary for any new disease. Several questions in the context of COVID-19 have been addressed including spectrum of disease severity (asymptomatic to fatal) 28…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in most studies patients with positive urine for COVID-19 were in severe clinical disease or needed oxygen supplement. On the other hand, no association has been reported between urinary symptoms and presence of virus in urine 2 while some investigators have reported a positive association between urine analysis and clinical severity of illness28 . The presence of proteinuria and microscopic hematuria has been associated with greater clinical severity of COVID-19 disease31 .…”
mentioning
confidence: 99%
“…Evaluation of Covid-19 severity and possible outcomes is limited by clinical heterogeneity and lack of speci c markers [1][2][3] Several laboratory parameters are considered in clinical practice, but the identi cation of novel indicators in blood specimens is a key issue for understanding the underlying biological mechanisms and improving prognostic accuracy [4][5][6][7][8][9] As a candidate marker we focused on the S100B protein, which is regarded to be involved in in ammatory processes as a Danger-Associated Molecular Patterns (DAMP) molecule [10,11]. S100B is a small acidic calcium-binding protein, originally isolated in the nervous system, where it is concentrated in astrocytes, being also present in oligodendrocytes, Schwann cells, enteric glial cells, and some neuron subpopulations [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One additional study looked at a combined outcome of disease severity and mortality. (18), (19), (20), (21), (22), (23), (24), (25), (26), (27), (28), (29), (30), (31), (32), (33), (34), (35), (36), (37), (38), (39), (40), (41), (42), (43), (44), (45), (46), (47), (48), (49), (50)…”
Section: Resultsmentioning
confidence: 99%